Sweet cherries from Fundão possess antidiabetic potential and protect human erythrocytes against oxidative damage. (May 2017) - Gonçalves, Ana C.; Bento, Catarina; Silva, Branca M.; Silva, Luís R.
Abstract: Cherries are one of the most appreciated summer fruits due to their attractive colour, sweet taste, high water content, low level of calories and composition in bioactive compounds which, in turn, are important to prevent some pathologies like diabetes, cardiovascular diseases and cancer. In this work we evaluated the phenolic profile and biological potential of 5 varieties of sweet cherries from Fundão region (Portugal) ( Saco, Sweetheart, Satin, Maring and Hedelfinger ). A total of 23 phenolic compounds were identified by LC-DAD and distributed by the several classes: 6 anthocyanins, 1 hydroxybenzoic acid, 8 hydroxycinnamic acids, 3 flavan-3-ols and 5 flavonols. Maring revealed higher contents in anthocyanins, while Hedelfinger was the richest in non-coloured phenolics. The antioxidant capacity was evaluated against DPPH and nitric oxide radicals. Hedelfinger was the most active against DPPH (IC50  = 12.1 μg/mL) and Maring against nitric oxide (IC50  = 140.9 μg/mL). Afterwards, antidiabetic capacity was evaluated through the inhibition of α -glucosidase activity, pointing Hedelfinger as the most active (IC50  = 10.3 μg/mL). The capacity of Saco extracts to inhibit the hemoglobin oxidation and the hemolysis of human erythrocytes was also evaluated. Both assays revealed a concentration-dependent inhibitory effect (IC50  = 38.6 μg/mL and IC50  = 73.0 μg/mL, respectively). The results obtained in this study allow us to conclude that sweet cherries possess a great biological potential, and further investigation should be done to promote commercialization and encourage its use in food supplements and in new pharmaceutical and nutraceutical applications. Graphical abstract: Highlights: Phenolic compounds of sweet cherries from Fundão Region Biological potential of sweet cherries First report about α -glucosidase inhibition activity First report about the protection of human erythrocytes